Classifying Services to Gain Strategic Marketing Insights - Lovelock, Christopher H. (Journal of Marketing, 1983)
The diversity of the service sector makes it difficult to come up with managerially useful generalizations concerning marketing practice in service organizations. This article argues for a focus on specific categories of services and proposes five schemes for classifying services in ways that transcend narrow industry boundaries. In each instance insights are offered into how the nature of the service might affect the marketing task.